Land- and water-based aerobic exercise program on health-related outcomes in breast cancer survivors (WaterMama): study protocol for a randomized clinical trial - Lima Alberton, Cristine; Siqueira Andrade, Luana; Botelho Xavier, Bruno Ezequiel; Guesser Pinheiro, Victor Hugo; Cuesta-Vargas, Antonio; Santana Pinto, Stephanie (BMC Springer Nature, 2024)
Background: Breast cancer is a prevalent form of cancer among women worldwide, often accompanied by physical and psychological side effects due to the disease and the treatment's aggressiveness. Regular physical exercise has emerged as a non-pharmacological approach to improve the quality of life of breast cancer survivors. We herein report the protocol of the WaterMama Study, which aims to evaluate the effects of land- or water-based aerobic exercise programs, compared to a health education program, on cancer-related fatigue and other health-related outcomes in breast cancer survivors. Methods: The WaterMama trial is a randomized, single-blinded, three-arm, parallel, superiority trial. We aim to recruit 48 women ≥ 18 years of age who have completed primary treatment for stage I-III breast cancer. Participants are randomly allocated in a 1:1:1 ratio to 12-week interventions of aerobic exercise training programs either in the aquatic or land environment (two weekly 45-min sessions) plus health education (a weekly 45-min session), or an active-control group receiving health education alone (a weekly 45-min session). The primary outcome is cancer-related fatigue, and the secondary outcomes include cardiorespiratory fitness, muscular performance, muscle morphology, functional capacity, mental health, cognitive function, pain, and quality of life. Outcomes assessments are conducted before and after the 12-week intervention period. The analysis plan will employ an intention-to-treat approach and per protocol criteria. Discussion: Our conceptual hypothesis is that both aerobic exercise programs will positively impact primary and secondary outcomes compared to the health education group alone. Additionally, due to its multi-component nature, we expect the aquatic exercise program promote more significant effects than the land exercise program on cancer-related fatigue, muscular outcomes, and pain.
Keywords: Ejercicio físico - Uso terapéutico; Aquatic exercise; Breast neoplasm; Cancer-related fatigue; Cognitive function; Mental health; Pain; Physical activity; Physical exercise; Physical fitness; Quality of life